(untitled) (Journal of history, 2019)
In this article, the authors, on the basis of ethnographic materials, attempted to uncover the ways and reasons for the deferred burials «amanatka koyu» («temporarily bury»), and their connection with aspects of the worldview of nomadic tribes, including the Kazakh people. They gave a description of the funeral rite of the deceased. Considered in the historical interrelation of the tradition of the burial of the Saka kings in the large pantheons, the burial of the Kazakh khans, biy rulers and batyrs in the mausoleum of Khoja Ahmet Yassaui, as well as the tradition of spreading the news of the death of influential people. In addition, considered the burial without a corpse (cenotaph) occurring in the Kazakh people.